Asymmetric and Harmonic Current Suppression of Dual Three-Phase PMSM Based on Double-Integral Sliding Mode Control - Jae-Ho Hyun; Syed Mohammad Maaz; Dong-Choon Lee; Dong-Hun Kim (IEEE Access)
Asymmetric and harmonic current components, primarily the fundamental, $5^{th}$ -, and $7^{th}$ -order harmonics, are inherent in asymmetric dual three-phase permanent magnet synchronous motors (DTP-PMSMs). These components reduce power efficiency and may cause system instability. To cope with these issues, in this study, a novel control scheme based on double-integral sliding mode control (DISMC) is proposed to suppress the asymmetric and harmonic current components. The proposed control scheme operates by managing the currents in the x-y subspace of vector space decomposition (VSD) stationary reference frame to zero. Therefore, the proposed control scheme significantly reduces the number of required controllers and eliminates the need for coordinate transformation. In addition, owing to its extra integral term, which offers superior performance in suppressing steady-state error, the proposed method delivers enhanced performance across the entire operating range compared to the widely used quasi-proportional-integral-resonance (Q-PIR) control. Furthermore, unlike resonant controllers that require variable gains, this method employs a fixed gain, resulting in reduced current oscillations during transient conditions. Detailed simulation and experimental results have confirmed the validity and effectiveness of the proposed method.